2005
DOI: 10.1159/000084344
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Stimulation for Faecal Incontinence

Abstract: Faecal incontinence is a common problem. Conservative measures are effective in a significant proportion of patients. Failure of conservative management has until recently meant recourse to surgical intervention. Surgical treatment is often associated with disappointing results. Recently, sacral nerve stimulation (SNS) has been developed as a minimally invasive, effective technique for idiopathic and acquired faecal incontinence. The technique uses chronic low-level electrical stimulation of the sacral nerves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Thus, the presence of an external sphincter defect (up to 120°) did not compromise the results of sacral nerve stimulation, as others have shown. 5,29 Furthermore, the outcome of SNS for fecal incontinence in patients having sphincter defects was equivalent to those having intact sphincter. There was no significant difference between an EAS defect of <90°and one of 90°to 120°of the circumference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the presence of an external sphincter defect (up to 120°) did not compromise the results of sacral nerve stimulation, as others have shown. 5,29 Furthermore, the outcome of SNS for fecal incontinence in patients having sphincter defects was equivalent to those having intact sphincter. There was no significant difference between an EAS defect of <90°and one of 90°to 120°of the circumference.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] With the good prediction by PNE, even patients with limited structural defects of internal and external anal sphincters have been included for sacral nerve stimulation, but most of them were not separately analyzed. 4,7,27,28 Recently studies have been published on patients with external anal sphincter defects 5,29 or internal anal sphincter disruption 30 with encouraging results. Guercerol et al 31 studied the factors associated with the success of PNE and SNS and found that there was no difference between the responders and nonresponders with regard to the presence of anal sphincter defect on anal ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…It has been tested on a variety of patients suffering from faecal incontinence due to sphincteric injury, neuronal damage and idiopathic incontinence and studies have shown that up to 80% of patients experience markedly improved function after implantation of the stimulator [77,78].…”
Section: Nerve Stimulationmentioning
confidence: 99%
“…Since the introduction of SNM for fecal incontinence (FI) reported by Matzel et al 1 in 1995, a large number of studies have shown positive results of SNM treatment for FI. [2][3][4][5][6] Another area in which SNM has shown promising results is constipation. 7-10 SNM has also recently been used to treat functional anorectal and pelvic pain.…”
mentioning
confidence: 99%